SkQ1 Ophthalmic Solution for Dry Eye Treatment: Results of a Phase 2 Safety and Efficacy Clinical Study in the Environment and During Challenge in the Controlled Adverse Environment Model. Issue 1 (January 2016) - Petrov, Anton; Perekhvatova, Natalia; Skulachev, Maxim; Stein, Linda; Ousler, George
Abstract Introduction This Phase 2 clinical trial assessed the efficacy and safety of the novel antioxidative, renewable compound SkQ1 for topical treatment of dry eye signs and symptoms. Methods In a single-center, randomized, double-masked, placebo-controlled, 29-day study, 91 subjects with mild to moderate dry eye instilled the study drug twice daily and recorded dry eye symptoms daily. Subjects were randomized 1:1:1 into one of three ophthalmic solution treatment groups: SkQ1 1.55 µg/mL, SkQ1 0.155 µg/mL, or 0.0 µg/mL (placebo). Subjects were exposed to a controlled adverse environment chamber at 3 of the 4 study visits (Day −7, Day 1, and Day 29). Investigator assessments occurred at all study visits. Results SkQ1 was safe and efficacious in treating dry eye signs and symptoms. Statistically significant improvements with SkQ1 compared to placebo occurred for the dry eye signs of corneal fluorescein staining and lissamine green staining in the central region and lid margin redness, and for the dry eye symptoms of ocular discomfort, dryness, and grittiness. In addition, SkQ1 demonstrated greater efficacy compared to placebo, although the differences were not statistically significant, for corneal fluorescein staining in other regions and/or time points (total staining score, central region, corneal sum score, and temporal region), lissamine green staining for the central and nasal regions, and blink rate scores. Conclusions This Phase 2 study indicated that SkQ1 is safe and efficacious for the treatment of dry eye signs and symptoms and supported previous study results. Trial registration Clinicaltrials.gov identifier: NCT02121301. Funding Miotech S.A.